The Association Between Hospital Characteristics and Nonresponse in an Organization Survey: An Analysis of the National Healthcare Establishment and Workforce Survey in Malaysia. Issue 1 (March 2019) - Foo, Chee Yoong; Reidpath, Daniel D.; Sivasampu, Sheamini
In any survey where some of the invited participants fail to respond estimates may be biased. The literature on survey nonresponse is substantial, and the intellectual focus has typically been on the nonresponse of individuals. An important yet less scrutinized area in the analysis of nonresponse is in organizational surveys, particularly surveys of health-care organizations. This study used data from the 2010 National Healthcare Establishment and Workforce Survey in Malaysia to examine the relationship between a set of measurable hospital attributes and their probability of survey response and the relationship between this probability and the differences in survey estimates. We found that readily measurable hospital characteristics such as size and geographical location are useful predictors of survey response likelihood. Larger hospitals and hospitals located in less developed geographical regions responded more favorably than their counterparts. We have also illustrated that the resulting response pattern affected some key survey estimates. These findings have the potential to extend our understanding of nonresponse to organization surveys in the health-care sector, potentially allow for the prediction of nonresponse, and help researchers to identify profiles of "reluctant responders" before a survey commences, so that additional engagement strategies may be used.